Nutritional and physicochemical qualities of thua nao (thai traditional fermented soybean) - Dajanta K. (2014)
The content of total phenolics, DPPH-free radical scavenging effect, total antioxidant and antimicrobial activities of Thua Nao, a Thai traditional fermented soybean, collected from six local markets in Chiang Mai, Thailand were investigated. In addition, their physicochemical and microbiological qualities were also evaluated. Based on the proximate analysis results, some variations were found among these Thua Nao products. In general, the samples contained 57.22 - 64.78% moisture, 4.70 - 5.44% ash, 12.92 - 28.06% crude fibre, 38.94 - 42.06% crude protein and 20.37 - 25.22% fat. For microbiological quality, total viable counts were in the range of 9.57 - 10.59 log CFU/g. Bacterial spore count was over 91% in all samples indicating that spore-forming bacteria are predominant for Thua Nao fermentation. Total phenolic contents of Thua Nao extracts were also varied depending on the source; these were between 30.46 - 44.58 mg GAE/g extract. For antioxidant activity, the IC 50 values as determined by the DPPH method ranged from 2.43 to 3.19 mg/mL of sample extract whereas total antioxidant activity as analysed by the carotene linoleate system were between 47.21 and 59.45% at 10 mg/mL of sample extract. Differences of these properties may be due to soybean variety, fermentation process, and starter organisms. In terms of antimicrobial activity, it was showed that the methanolic extracts of Thua Nao could inhibit only Bacillus cereus. Our study provides detailed information regarding nutritive quality of Thua Nao. The product appears to be a good protein source based on protein content and potent to antioxidant diet food with the great contents of antioxidant phytochemicals and their strong antioxidant activities.